2013
DOI: 10.1021/cs300636j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Consequences of Particle Size and Chloride Promotion in the Ring-Opening of Cyclopentane on Pt/Al2O3

Abstract: Ring-opening of cyclopentane on alumina-supported Pt particles was studied as a function of Pt particle size in the presence of different Cl contents. With catalysts prepared from a Cl-free precursor, measured turnover rates increased monotonically with increasing Pt particle size (1–15 nm). On catalysts derived from a Cl-containing precursor, the turnover rates fell into two separate trends with the change of Pt particle size, depending on the extent of Cl removal by increasing thermal treatment temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…It has been well documented that impurities such as alkali metals (e.g., Na + ) can substantially modify the thermal stabilities of γ-Al 2 O 3 and also influence its phase transformations [11,13,14,[26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that impurities such as alkali metals (e.g., Na + ) can substantially modify the thermal stabilities of γ-Al 2 O 3 and also influence its phase transformations [11,13,14,[26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the prepared crystallites have different relative ratios of specific facets allowing systematic studies aimed at finding correlations between phase transformations of γ-Al 2 O 3 and crystallite morphologies that otherwise would be very difficult with commercial γ-Al 2 O 3. These information will be very useful for potential development of thermally stable γ-Al 2 O 3 without any surface modifier such as La, Ba, etc., that can affect the catalytic properties [11,[13][14][15][16][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the ionic state of platinum in alumina-platinum catalysts were first reported in [10] and then verified by others [5,11]. Modern ideas on the structure of platinum catalysts dictate an essential role for ionic platinum species in catalyzing the transformation of hydrocarbons [12]. Such ionic platinum species show an order of magnitude higher atomic activity towards the aromatization of n-alkanes when compared with disperse Pt 0 [13].…”
Section: Introductionmentioning
confidence: 87%
“…ThePt δ + species have been suggested play a positive role in the hydrogenation of toluene. Shi et al [19] have observed a higher activity of the Pt/Al 2 O 3 catalyst obtained by impregnation with Cl-containing precursor in the ring opening of cyclopentane as compared to the one obtained by impregnation with Cl-free precursor (Pt(NH 3 ) 4 (NO 3 ) 2 ). In contrast, the activity enhancement was less marked when a similar concentration of Cl was introduced to the catalyst by means of postimpregnation.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the Pt catalysts is based on a high-temperature reduction step with H 2 . It was shownthat even after the heat treatment, not only platinum species, but also residualions originatingfrom theactive metalprecursor can still be found on the catalystsurface [18,19]. Those residues can influence the catalyst performance.…”
Section: Introductionmentioning
confidence: 99%